Awareness and Attitudes of Health Workers About Breastfeeding and Baby Friendly Hospital Practices - (:unkn) unknown (My University, 2020)
Objective: Baby Friendly Hospital Initiative (BFHI) programme was developed to train health workers, to promote and support breastfeeding. Healthcare providers play a key role in the beginning and continuity in breastfeeding. This study was carried out to determine the knowledge and awareness of health workers about breastfeeding and BFHI. Material and Methods: This descriptive study was carried out in 4 different hospitals among health workers (residents, nurses, midwives and specialized physicians). An interview with a structured questionnaire was applied to health workers via face to face. Results: Of 269 participants, 143 (53.1%) were residents, 72 (26.7%) were nurses 54 (20.0%) were specialized physicians. Of all participants 39.3% had training on breastfeeding at their institution. Almost half of the health workers knew the definition of Baby Friendly Hospital and 21.6% of them knew Code of Marketing of Breast Milk Substitutes. Knowledge about baby friendly hospital initiative and international code of marketing of breast milk substitutes was significantly lower among residents than specialist and nurses. Of all participants, 51.7% felt themselves proficient about breastfeeding. Feeling proficient was significantly high among nurses. Requesting training on breastfeeding was 74.7% among all participants and residents requested training about breastfeeding more than two other professions. Conclusion: Our study showed that most of the health workers did not have proper training about breastfeeding and BFHI. There were significant differences in the level of awareness between professions. Curriculum of the medical schools and in-service trainings of health workers should be improved in relation to BFHI and breastfeeding practices.

Amaç: Bebek Dostu Hastane Girişimi programı emzirmenin başlatılması ve sürdürülmesi için sağlık çalışanlarının eğitilmesi için geliştirilmiştir. Sağlık çalışanları emzirmenin başlatılması ve devamında anahtar rol oynamaktadırlar. Çalışmamızın amacı, sağlık çalışanlarının anne sütü ve emzirme hakkındaki bilgi düzeyi ve farkındalıklarını saptamaktır. Gereç ve Yöntemler: Çalışmamız tanımlayıcı bir çalışmadır. Dört farklı hastanede sağlık çalışanları (asistan doktor, hemşire, ebe, uzman doktor) arasında yapılmıştır. Sağlık çalışanlarına yüz yüze görüşme ile yapılandırılmış bir anket uygulanmıştır. Bulgular: İki yüz altmış dokuz katılımcının 143 (%53,1)’ü asistan doktor, 72 (%26,7)’si hemşire, 54 (%20,0)’ü uzman doktor idi. Katılımcıların %39,3’ü çalıştığı kurumda emzirme eğitimi almıştır. Sağlık çalışanlarının neredeyse yarısı Bebek Dostu Hastane kavramını, %21,6’sı Uluslararası Mama Kodu’nu bilmekteydi. Bebek dostu hastane girişimi ve uluslararası mama kodunu bilme oranları asistan doktorlarda, hemşire ve uzman doktorlara oranla daha düşük idi. Katılımcılardan %51,7’si kendini emzirme konusunda yeterli görmekteydi, bu oran hemşirelerde belirgin oranda yüksek idi. Tüm katılımcılar arasında emzirme konusunda eğitim almayı isteme oranı %74,7 idi, asistan doktorların bu konuda eğitim isteme oranları diğer iki gruba göre daha yüksek idi. Sonuç: Çalışmamızın sonuçlarına göre sağlık çalışanları emzirme ve bebek dostu hastane girişimi konusunda düzenli eğitim almamaktadırlar. Sonuçlarımıza göre meslek grupları arasında farkındalık düzeylerinde anlamlı farklılıklar bulunmaktadır. Tıp fakültelerinin eğitim müfredatı ve sağlık çalışanlarının hizmet içi eğitimleri, emzirme pratikleri ve bebek dostu hastane girişimi uygulaması açısından geliştirilmelidir.
Sağlık Çalışanlarının Emzirme ve Bebek Dostu Hastane Pratikleri Açısından Farkındalık ve Tutumları